Model for the Automated Generation of Optimized Work Packages in Results-Based-Finance Mega Sanitation Projects - Shalaby, Amira Mohamed Hasan (AUC Knowledge Fountain, 2021)
The sanitation sector is one of the critical sectors in any country. The lack of proper sanitation systems causes many environmental hazards that threaten people’s health and well-being. In many developing countries, the sanitation sector constitutes a significant part of their strategic plans of reform. However, with the public treasury’s very limited budget, countries opt to major lending institutions for funds. “Results-Based-Finance” is a new funding mechanism used by many lending institutions. The mechanism has proven its efficiency in achieving the necessary reform in sanitation sectors. Due to the complexity of the funding tool, it is crucial to be able to decompose the project into smaller packages to be able to manage and control the project effectively. The objective of this dissertation is to reach an optimum packaging scheme that enables mega sanitation infrastructure projects to be successfully managed through better planning and cost control practices. The model aim shall be to minimize the amount of funds needed from the borrowing country through three options: by reducing the peak value of the negative cashflow curve, by normalizing the negative cashflow curve, or by a combination of the previous two objectives. With the aid of Unified Modelling Language (UML), an algorithm is developed to map the logic behind the model suggested with detailed illustrations of its different modules. Object-oriented processes and operations are modeled using various diagrams of the language, which automatically generate the optimum packaging combination. The packaging model is then implemented via a number of computer-aided programs. Microsoft Excel is used for calculation purposes. Visual Basic for Applications (VBA) programming language is used to make the model user-friendly for non-engineering stakeholders. Palisade's Decision Tools Suite is used for the genetic algorithm optimization process. In order to verify the model, different approaches have been used, which include system checks to minimize programming errors. Moreover, a sensitivity analysis module has been designed with the aid of Top Rank software in order to ensure the flexibility and the capabilities of the constructed model. After the model verification is conducted, the model shall be validated using data from a case study of a mega sanitation results-based financed project located in Egypt. The project is achieved through the World Bank and aims to strengthen the Egyptian Institutions for better service delivery by providing incentives. The project worth is 550 Million USD. The ability of the model to plot the optimization process and the suggested outputs is proven feasible. The model output is not only the content of the packages but also a complete managing plan which demonstrates much useful information to the decision-makers and government officials. Moreover, the model has reduced the peak value of the negative cashflow curve by 18.7 percent, normalized the negative cashflow curve by 5.4 percent, and the model has reduced the funding gap in general by 8.9 percent.